The Antecedents of Individual Job Performance and Moderating Effect of Role Stress: Path Models on the Logistics Service Industry in Thailand - Tadokoro, Yuichi; Varma, Parvathy (Scholar: Human Sciences, 2021)
The research examined the effect of organizational justice, perceived organizational support on organizational commitment, and job performance and the moderating effect of role stress of employees in logistics service providers in Thailand. This research employed a path model utilizing structural equation modeling with multivariate techniques combining methods of factor analysis. The application of multi-group analysis clarified the moderating effects of role stress by grouping the low role stress group and high role stress group of respondents. Data was collected from 889 professional white-collar workers from 15 logistics service providers in Thailand. There are two groups that include the low role stress group (n=426) and high role stress group (n=433) of respondents which were segregated based on the median. This research revealed that perceived organizational support ultimately contributes to individuals’ job performance. The results indicated moderation effects of role stress, i.e. organizational justice is a significant factor that contributes to organizational commitment in high role stress group, unlike in low role stress group. Organizational commitment has significant negative effect on counterproductive work behavior in low role stress group, unlike in high role stress group. The findings can be inferred as organizational justice and support are perceived as benefits by individuals, which initiates the social exchange relationship then enhances job performance of the individuals in an organization via organizational commitment. This study has concrete managerial implications, such as by announcing and actualizing the flexible workplace can be an effective and efficient measures for the logistics service industry.